Abordagem sócio-jurídica sobre o consumismo na sociedade globalizada: agressão aos direitos humanos fundamentais de proteção da infância e juventude - Monte, Hilda Maria Couto (2016)
This work approach the aspects socio-legal of the consumerism childhood-adolescence and your aggression, through of the publicity vehicles, consumer culture and reification of the interpersonal relationship characteristics of the global world, against liberty of exercise of the legal institute of the Family Power, analyzing the thematic under the perspective interdisciplinary of the Frankfurt School. The proposal has turned out to be challenging, but of social importance and legal uncontested, therefore, through Several authors and researchers, was possible not only Tracing a panorama of current society, but include in this context the problem of the violation of childhood fundamental rights and young people, supported In the Doctrine of Integral Protection of minors, exhalted by the International Convention on the Rights of the Child and teenager of 1989, by federal constitution of 1988 and infra-constitutional norms. The need to establish propositions socio-legal and educational for best efficacy of the rights fundamental Inherent to family relationships between parents and children became imperative, not only for require a legal disciplining more specific about of the childhood-adolescence publicity control in the country, but also with the civil society participation, family and implementation of educational policies more appropriate and focused for the protection and well-being of childhood.